Penguatan Manajemen Mitigasi Bencana bagi Komunitas Siswa/I Sekolah Dasar dan Menengah Di Situs Air Terjun Sigerincing - Muyusari, Febra; Dwijaya Pratiwi, Yunita; Hopipah, Ria; Haliza, Zanur (PT. Meja Ilmiah Publikasi, 2026)
The Sigerincing Waterfall area, which is part of the Merangin Jambi UNESCO Global Geopark, has high potential for geological and tourism resources, but is located in an area prone to natural disasters such as floods, landslides, and earthquakes. This condition necessitates systematic efforts to enhance community capacity in disaster risk reduction. This research aims to analyze the effectiveness of community-based disaster mitigation management strengthening in increasing community awareness and preparedness in the geopark area. The research method used is a descriptive qualitative approach thru educational activities, socialization of the early warning system, participatory discussions, and field visits to the Indonesian Tsunami Early Warning System (ITEWS) facilities. The subjects of the activity include village officials, school personnel, the local community, and early warning system operators. The research results show that disaster mitigation activities are able to increase participants' understanding of potential hazards, early warning mechanisms, and the importance of local wisdom's role in disaster risk reduction. In addition, this activity also strengthens cross-sectoral coordination in building a sustainable disaster-aware culture in the geopark area. Thus, strengthening community-based disaster mitigation management is considered effective as a model for disaster education in disaster-prone areas.